Volatility of Japan's exchange rate and Malaysia's trade and FDI: a granger causality test / Muhammad Suffian Abdul Shukor - Abdul Shukor, Muhammad Suffian (2008)
The objective of this paper is to determine the relationships of Japan exchange rate volatility with the volatility of Malaysia's macroeconomic variables, namely trade and FDI. The paper presents empirical evidence that shows the relationship of Japan exchange rate volatility on Malaysia trade and Foreign Direct Investment (FDI) volatility. The independent variable is Japan exchange rate (Japanese yen to ringgit Malaysia) volatility and the dependent variable is Malaysia Trade (import and export with Japan) and FDI from Japan. The data collected are quarterly data between 1997 and 2007 and analyzed using Granger Causality Test. The volatility of the variables is measured using standard deviation of growth. After the data has been tested for stationary, the data then are tested in the Granger causality test. The test uses lag 1,2,4,8 and 12. According to the result of the test, there is no evidence of Granger-causes between Japan exchange rate and export to Japan in all lag chosen. For exchange rate volatility and. import to Japan volatility there is a unidirectional causality in lag 1 and bilateral causality in lag 8 and for Japan exchange rate volatility and FDI from Japan volatility, there is a unidirectional causality in lag 4 and 12 where FDI from Japan volatility Granger-causes exchange rate volatility.